2019
DOI: 10.1111/bjh.16013
|View full text |Cite
|
Sign up to set email alerts
|

Deferasirox reduces oxidative DNA damage in bone marrow cells from myelodysplastic patients and improves their differentiation capacity

Abstract: Patients with low-risk myelodysplastic syndromes (MDS) usually develop iron overload. This leads to a high level of oxidative stress in the bone marrow (BM) and increases haematopoietic cell dysfunction. Our objective was to analyse whether chelation with deferasirox (DFX) alleviates the consequences of oxidative stress and improves BM cell functionality. We analysed 13 iron-overloaded MDS patients' samples before and 4-10 months after treatment with DFX. Using multiparametric flow cytometry analysis, we measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Proteomic analysis also revealed an increase in protein carbonylation in erythroid precursors, which could be related to the increased DNA damage in MDS CD34+ cells [4,41]. Indeed, a recent study demonstrated an increase in DNA damage in MDS patients, which was reverted by treatment with an iron chelator [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteomic analysis also revealed an increase in protein carbonylation in erythroid precursors, which could be related to the increased DNA damage in MDS CD34+ cells [4,41]. Indeed, a recent study demonstrated an increase in DNA damage in MDS patients, which was reverted by treatment with an iron chelator [6].…”
Section: Discussionmentioning
confidence: 99%
“…Previous assessments of oxidative stress in BM of patients with MDS using antioxidant biomarkers showed that all BM cell types have an imbalance in ROS levels that is related to lower overall survival [6,10,42]. This phenotype was also reverted by iron chelation [6,42], suggesting that amelioration of the oxidative stress effects by DFX treatment is beneficial for these patients. Indeed, an improvement in the pathogenesis of MDS has previously been reported after DFX therapy [20,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell clonogenic capacity was analyzed by colony-forming unit (or CFU) assays in semisolid methylcellulose medium as previously described [30]. K562 and KCL22 cells or primary bone marrow mononuclear cells (BM-MNC) from CML patients were treated with two different TKIs (either imatinib or nilotinib), allopurinol, and their combinations in RPMI medium for 48 h. Cells were then washed with PBS and 500 K562 and KCL22 cells, or 12500 BM-MNC cells were resuspended in 500 µL of "HSC-CFU-basic" or "HSC-CFU-complete w/o Epo," respectively (Miltenyi Biotec; Madrid, Spain) and seeded on a culture plate.…”
Section: Colony Forming Unit Assaysmentioning
confidence: 99%
“…In the work published in this issue of the British Journal of Haematology, Jiménez‐Solas et al () explored this question in an elegant work on primary samples from MDS patients.…”
mentioning
confidence: 99%